2018
DOI: 10.1111/gfs.12394
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis and in situ ruminal degradation of lucerne ensiled with Cistus ladanifer tannins

Abstract: The effects of ensiling lucerne with graded inclusion of Cistus ladanifer condensed tannins (CT) on in silo fermentative parameters, in vitro organic matter digestibility (IVOMD) and on in situ rumen degradability of dry matter (DM) and crude protein (CP) were studied. Lucerne forage (Medicago sativa subsp. sativa) was sprayed with different solutions of C. ladanifer CT extract in 60 ml of water in order for dose 0 (control), 40 (L40), 80 (L80) and 120 (L120) g of CT per kg of lucerne DM and was ensiled in lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Reductions in the degradation rate of nitrogen fractions from 34 days can reduce the amount of ammonia nitrogen available to rumen microorganisms, which use it for the synthesis of amino acids, cell structures, and growth (25) , which negatively impacts the DM degradability (Table 2). In tropical grasses, a reduction in the protein degradation rate is expected with advancing age, associated with factors such as climate, water availability, and temperature, with the incorporation of this fraction in the less soluble components of the forage (1,13) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in the degradation rate of nitrogen fractions from 34 days can reduce the amount of ammonia nitrogen available to rumen microorganisms, which use it for the synthesis of amino acids, cell structures, and growth (25) , which negatively impacts the DM degradability (Table 2). In tropical grasses, a reduction in the protein degradation rate is expected with advancing age, associated with factors such as climate, water availability, and temperature, with the incorporation of this fraction in the less soluble components of the forage (1,13) .…”
Section: Resultsmentioning
confidence: 99%
“…The level of rumen degradability of CP can be variable between different forage species, which determines the availability of ammonia nitrogen in the rumen, and the proportion of amino acids from the diet and microbial protein, that reach the intestine, which are directed to tissue protein synthesis (25) . The concentration of crude protein is higher at the vegetative stages of forages and decline at the flowering stage, which may vary depending on differences between species, initial level of protein in the plant, stem and leaf proportions, content of fiber components in the cell wall and ambient temperature (15,21) .…”
Section: Resultsmentioning
confidence: 99%
“…AN is produced by clostridial fermentation, and one of the criteria for good silage is AN < 100 g/kg TN ( Mu et al, 2020 ). NPN is an important product of proteolysis, and the utilization rate of NPN in ruminants is lower compared with that of TP due to rapid degradation ( Dentinho et al, 2019 ; Wang et al, 2021 ). The present study suggested that the addition of malic acid and cellulase had positive effects on inhibiting proteolysis, and low pH was speculated to inhibit the activities of proteases ( He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, one of the most important biochemical reactions is proteolysis, which transforms proteins into NPN (such as small peptides, free amino acid, and AN) under the activities of microorganisms and proteases [ 43 ]. The conversion of TP to NPN (PA fraction) reduces the N utilization in ruminants, further increasing urinary and fecal N losses and causing environmental pollution [ 44 ]. Thus, the application of malic acid may have a good effect in terms of nutrient preservation.…”
Section: Discussionmentioning
confidence: 99%